An Overview of the Phenomenon of Sports Violence in Tarkam Soccer Matches in South Sulawesi Through the Perspective of Players Towards Organizers and Supporters - Sulaeman; Abdul Rahman; Arfandi Akkase (Universitas Muhammadiyah Palu, 2024)
This research aims to determine the description of the phenomenon of sports violence in tarkam football matches in South Sulawesi through the perspective of players against the committee and against supporters. This type of research is descriptive-quantitative, where the focus of the research is to find out whether the tarkam soccer match in South Sulawesi is still synonymous with acts of violence or has developed into a gripping match that is more professional and away from acts of violence. The population of this study were all soccer players in South Sulawesi who regularly participated in soccer matches, while sampling in this study used accidental sampling techniques. Data collection techniques by distributing questionnaires, where the questionnaire in this study was a mixed questionnaire. The results showed that 91.3 percent of respondents stated that they had seen violence in football involving players and supporters of the opposing team, but 72 percent of respondents stated that they were not directly involved in violent football matches with supporters of the opposing team. Furthermore, the study showed that 58.7 percent of respondents had seen violence in football matches involving players with the organizing committee, but 81.7 respondents stated that they were not directly involved in the violence in football matches with the organizing committee. So it can be concluded that violence in the tarkam football tournament in South Sulawesi involving players with supporters and the organizing committee still often occurs.